Analisis Kontribusi Pendapatan Sektor Pariwisata terhadap Produk Domestik Regional Bruto (PDRB) di Kabupaten Simalungun - Tryana Ramadhany Batubara; Juliana Nasution; Rahmat Daim Harahap (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study aims to determine and analyze the contribution of tourism sector revenue to regional gross domestic product in Simalungun Regency. The type of research used is this research, namely qualitative research. Types and sources of data using a qualitative approach with secondary data obtained from the Central Statistics Agency of Simalungun Regency. The results showed that the occupancy rate of star hotel rooms and other inns in Simalungun Regency increased to 27.93 percent in 2018. Thereafter it has decreased every year from 2019 to 2021 to 18.02 percent. The number of hotels and other lodgings in Simalungun Regency in 2021 is 74. The number of hotel rooms and other lodgings in Simalungun Regency in 2021 is 1,891 rooms. The number of beds in hotels and other inns in Simalungun Regency in 2021 is 2,859 beds. The average length of stay for foreign guests in 2021 is 1.59 days while domestic guests are 1.14 days. Keywords: Simalungun Regency, Accommodation and Hotels